KINERJA TIM PENGAWASAN DAN PEMBINAAN TERTIB NIAGA PADA PERIZINAN PERGUDANGAN KOTA PEKANBARU - Kardianto, Dicky; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
AbstractSupervision and Development Team Pekanbaru City Commercial Conduct established by the Head of Department of Trade and Industry, the city of Pekanbaru in order to smooth the supervision and guidance order in trade on the licensing and non-licensing and warehousing. The purpose of this study was to determine how performance monitoring and coaching team order in trade in Pekanbaru City licensing warehousing and factors that hinder. The theory used is Lenvine theory that there are three indicators to measure the performance of public sector organizations, namely: Responsiveness, Responsibility, and Accountability. This study used a qualitative method with case study approach and the necessary data both primary and secondary obtained through interview, observation and documentation for further analysis. The results showed that: first, the indicators of the responsiveness of Team Performance Supervision and Development of Conduct Commerce on Licensing Warehousing Pekanbaru City has not been carried out in accordance with the standards, the indicators of responsibility can be concluded that there is still not running as it should, and the indicators of akuntablitias can be concluded that there is still run in accordance with the set target. Second, the factors that hinder the Supervision and Development Team Performance Conduct Licensing Commerce In Pekanbaru City Warehousing namely: Human Resources, Disposition Implementor and lack of awareness and knowledge of the owner of the warehouse.* Keywords : Organizational Performance, Supervision, Guidance, Warehousing